Peroneal Tendoscopy: Applied Anatomy and Operative Technique - Panagiotis D Symeonidis; Ioannis Spanos; Pim AD van Dijk; Niek C van Dijk (Journal of Foot and Ankle Surgery (Asia Pacific))
Pathologies related to the peroneal tendons are responsible for the largest percentage of retrofibular ankle pain, including a wide spectrum of relevant diagnoses. Diagnosing peroneal tendon pathologies, however, remains challenging as the accuracy of imaging studies including ultrasound (US) and magnetic resonance imaging (MRI) is still limited by constricting factors including operator dependence for US and the magic angle effect in MRI. On the contrary, advances in technology and our knowledge of the regional anatomy have rendered tendoscopy a viable option for patients with a high clinical suspicion for peroneal tendon pathology but a lack of positive findings on imaging. For both diagnosis and treatment of these patients, peroneal tendoscopy is recommended. The aim of the current study is to present a step-by-step, state of the art manner to perform a peroneal tendoscopy in a safe and reproducible manner. As indications of the method expand, an increasing number of surgeons with experience in foot and ankle arthroscopy have the chance to incorporate peroneal tendoscopy in their armamentarium. A detailed description of the operative technique with reference to recent data from anatomical and cadaveric studies is presented. Moreover, tips and pearls from the authors’ accumulated experience are being highlighted. Finally, common pitfalls and limitations of the method are being discussed.